Development of Electronic Student Work-Sheets (E-LKPD) by Digital Drawing Mode at Private Vocational Schools - Meilisa, Meilisa; Tristantie, Nining; Nitami, Dita Dwi (Pedagonal : Jurnal Ilmiah Pendidikan, 2024)
This research emerged from several obstacles in the field, namely students' difficulties in understanding digital technical design material with Ibis Paint. The aims of this research are : 1) to develop an E-LKPD for digital fashion drawing at Private Vocational School, 2) to determine the feasibility of a digital fashion drawing E-LKPD. This research used the RD method with a 4-D development model (define, design, development, and disseminate). The validation and trial stages were carried out to assess the feasibility of E-LKPD. Material experts and media experts play a role in validation to obtain input regarding the appropriateness in terms of material and media. The feasibility test was carried out through a questionnaire to class XI students at Setia Budi Binjai Private Vocational School, second semester. Data analysis uses a five-scale score (Likert scale) for the predetermined assessment categories. The results of this research are: 1) validation of E-LKPD drawing mode according to material experts "Very Good" with an average percentage score of 94% and according to media experts "Very Good" with an average percentage score of 87.4%. 2) The feasibility of E-LKPD drawing mode is included in the "Very Good" category. The average score percentage results in the small group trial were 80% with "Good" criteria, the medium group was 87.5% with "Very Good" criteria, and the large group was 92.8% with "Very Good" criteria.